Casual Attribution and Its Relation with The Scholastic Achievement Motivation on A Sample of Superior and Ordinary Students in Lattakia Governorate. - Barakat, Kassan; Slmoun, Reem; Doukhoul, Mouneem (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
This research aimed at knowing the relation between casual attribution, and scholastic Achievement Motivation on a sample of superior And ordinary students, and at knowing the differences between the two sorts of each sample the research depended on the descriptive and analytic method by using casual attribution scale which has been designed by the researcher the sample was (288) students of males and females from the eighth grade at schools of superior And ordinary in Lattakia governorate: The results were as follows: There is a statistical significant positive correlative relation between attribution of (effort making) and scholastic Achievement Motivation of ordinary students students while there is no statistical significant correlative relation between the other casual attributions (the ability, the luck (chance), the task difficulty, (the mixed attribution) and scholastic Achievement Motivation. There is a statistical significant positive correlative relation between each of (the ability attribution, the effort attribution, the task difficulty attribution, and between scholastic Achievement Motivation of superior students, while there is no statistical significant correlative relation between, the luck attribution, and the mixed attribution, and scholastic Achievement Motivation. There are statistical significant differences between the mean scores of ordinary students responses and superior students ones according to casual attribution scale except for the mixed attribution, and there are differences according to scholastic Achievement Motivation scale in favor of the superior students. There are no a statistical significant differences between the mean scores of male students responses and female students ones according to both scales the casual attribution and scholastic Achievement Motivation.